Dança: arquivos como invenções - Thembi Rosa Leste (2020)
The research in Dance: Archives as Inventions concerns digital platforms related to contemporary dance, analyzing how digital media has reconfigured the notion of archive. Projects carried out in this field, such as Synchronous Objects (2009); Motion Bank (2010-2013); Choreographic Coding Labs, CCLs have demonstrated that choreography archives are not merely an attempt to faithfully represent the artistic works. Many projects in this broad area are proposing the creation of choreographic objects, breaking with the paradigms of representation, the neuroses of vanishing on dance and inaugurating new perspectives related to the fluidity and dynamicity of archives (Wolfgang Ernst; Maaike Bleeker are some authors engaged on this idea). Archive Fever, Derrida’s proposition supports the question about what is an archive and sustains the impossibility of having uniqueness on this concept. It also emphasizes that the archiving produces and records the event, so it is related to its future. Thus, online collections, digital dance archives, MOCAP and other tracking systems can turn choreography into data in order to make it able to be remade and reinvented in many different forms. Alongside, André Lepecki’s proposition of the body as archive, and the distinction between archive and repertoire by Diana Taylor are adopted in this research with the aim to investigate the premise of archives as inventions. Assuming both concepts, the body as archive and the choreographic objects, proposed by Scott deLahunta, James Leach, Sarah Whatley, William Forsythe, leads to considering them as practices that are extending the notions of choreography and archives, in interrelations with digital media. Building digital dance platforms means to expand endeavors related to choreography and in particular to further develop connections with different fields of knowledge, as well as instigating conversations related to dance with a wider audience. This research project acts at the intersection between theoretical and practice-based fields, focusing on dance creative process in synergy with digital platforms. This interweaving of fields and practice reinforces and deepens the notions of dance as knowledge and archives as inventions.